Descriptive Epidemiology of Brain and Central Nervous System Tumours: Results from Iran National Cancer Registry, 2010-2014. (18th September 2020) - Salimi, Amir; Zali, Alireza; Seddighi, Amir Saeid; Seddighi, Afsoun; Meshkat, Shakila; Hosseini, Morteza; Nikouei, Amir; Akbari, Mohammad Esmaeil
Abstract : Background . Central nervous system (CNS) tumours account for only 1-2% of cancer incidence but are a major reason for mortality and morbidity due to malignancies. Recent studies show an increase in the rate of CNS tumours worldwide, especially in developing countries. Moreover, there is significant heterogeneity in epidemiological patterns worldwide. This study is aimed at representing nationwide epidemiology of CNS tumours in Iran. Methods . Iran National Cancer Registry 2010-2014 data were reviewed for CNS tumours. The epidemiological rates were calculated for both genders and all age groups using the 2011 census information. Results . Out of 17345 cases, 58.5% were men and 41.5% were women. The mean age was 45.55 years ranging from less than 1 month to 100 years old. Average total age-standardized incidence rate (ASR) was 5.19 for primary tumours. The annual percent change (APC) was 14.23% during the study period. The most frequent site and histology recorded were brain, NOS and diffuse astrocytic, respectively. Geographical distribution showed about five-fold difference in ASRs between different provinces. Conclusion . The overall ASR calculated was higher than the global rate in 2012 but lower than that of most developed countries, showing an increasing trend which may be due to either advances in diagnosing or risk factor augmentation. The mean age and incident rates were higher than those of previous reports in Iran.